Structural health monitoring in adhesively bonded composite joints - Caldwell, Steven, author; Radford, Donald W., advisor; Simske, Steven, committee member; Cale, James, committee member; Adams, Henry, committee member (Colorado State University. Libraries, 2024)
Composite bonded aircraft structure is a prevalent portion of today's aircraft structural composition. Adequate bond integrity is a critical aspect of the fabrication and operational service life of aircraft structure. Many of these structural bonds are critical for flight safety. Thus, a major concern is related to the assurance of quality in the structural bond. Over the last decade, non-destructive bond evaluation techniques have improved but still cannot detect a structurally weak bond that exhibits full adherend/adhesive contact. Currently, expensive, and time-consuming structural proof testing is required to verify bond integrity. The objective of this work is to investigate the feasibility of bondline integrity monitoring via piezoelectric sensors embedded in the composite joint. Initially, a complex composite joint, the Pi preform, was analytically evaluated for health monitoring viability, with the results showing promising capability. Subsequently, due to experimental complexities, a simple, state-of-the-art composite single lap shear joint is selected for experimentation and analysis to measure and quantify the effect of incorporating a sensor within the bondline to evaluate and expand on the ability of the embedded sensor to monitor and assess the joint integrity. Simple flatwise tension joints are also studied to investigate an orthogonal loading direction through the sensor. The experimental results indicate that the embedded piezoelectric sensors can measure a change in the joint before the integrity degrades and fails on subsequent loadings, resulting in a novel approach for prognostic performance evaluation without detrimentally affecting the performance of the structural joint.
Keywords: electromechanical impedance; single lap shear joint; composite bond; structural health monitoring; piezoelectric sensor